Toward quality assessment of 3D printed oral dosage forms. Issue 1 (January 2018) - Markl, Daniel; Zeitler, Axel; Rades, Thomas; Rantanen, Jukka; Bøtker, Johan
The additive manufacturing industry achieved a corporate annual growth rate of 25.9% according to the Forbes analysis of the Wohlers Report 2016. This high growth rate is placed in perspective when looking at the past 27 years where the corporate annual growth rate has averaged 26.2% each year indicating that additive manufacturing is clearly a growing industry. Such growth needs to be supported by suitable quality testing methods: with the economic success achieved in this market and the associated transition from mass production toward mass customization comes the need for new and innovative methods to assess the quality of the 3D printed geometries. This will be especially important for pharmaceutical products where a sub-standard quality of the final product can have detrimental consequences for patient health and safety.